Mouse Enterocytes' Membrane Permeability to Water and Cryoprotective Agents - Ogurtsova, Viktoriia V.; Kovalenko, Igor F. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):164.